A ghostly playmate - Spenser, M. D.; Copyright Paperback Collection (Library of Congress) (Plantation, Fla. : Paradise Press, 1997)
Virginia's best friend is a ghost who plays games with her and won't let her quit. The ghost wants her as a playmate forever.
Keywords: Ghosts -- Juvenile fiction; Horror stories